Porous structures for use, for example, in filters and their manufacture
By filling the glass tightly and bonding each other, it is also introduced into the cracking mechanism to form a high porosity and porous structure, which solves the problem that the existing glass bubble is difficult to form an open pore degree, and improves the performance of the application and other applications.
Patent Information
- Application Number
- CN202080099622.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-04-07
AI Technical Summary
It is difficult for existing glass bubbles to form efficient open porous structures in the structure, which limits their performance in applications such as filters.
By filling the glass tightly and bonding each other, it is introduced into the cracking mechanism to open the cave of a single glass bubble to form each other, forming an extension of the porous structure and reaching its surface cavity. This process includes squeezing, heating and cooling steps to control the bonding and cracks of glass bubbles.
The formation of high pores and porous structures improves the performance of filters and other applications, such as enhancing the filtration efficiency and the density of the channel.
Smart Images

Figure CN115427374B_ABST
Abstract
Description
Background Art
[0001] Aspects of the present disclosure are generally directed to structures formed from breached glass bubbles and which may be used in filters.
[0002] Tiny glass bubbles (also called microballoons or hollow glass "microspheres") are commercially available from companies such as Dennert Poraver, 3M, FibreGlast Developments Corp, and Potters Industries LLC. Such glass bubbles can be used as fillers in composite materials such as concrete.
[0003] Glass bubbles can be characterized by "diameter," where diameter refers to the diameter if the volume of the glass bubble is arranged in a perfect spherical geometry. However, in practice, glass bubbles may only be approximately spherical, such as having a potato shape. The size of the glass bubbles can be selected and characterized based on diameter, where the "D50" particle size corresponds to the 50% pass-through point of glass bubbles with a diameter of that D50 value, where half of the diameters in the group are greater than the D50 value and half of the diameters are less than the D50 value. Similarly, "d50" corresponds to the 50% pore size of the porous structure, and d10 corresponds to the 10% pass-through point, as measured by mercury intrusion via ASTM standards. Thus, the ratio of (d50-d10) / d50 provides insight into the pore size.
[0004] Glass bubbles are generally brittle, and conventional practice teaches methods to prevent breakage of the glass bubbles thereby maintaining the internal closed cavity of the glass bubbles, preserving the low weight-volume relationship that the glass bubbles can provide. When the integrity of the glass bubbles is maintained, the glass bubbles can be incorporated into composite materials for buoyant load-bearing structures, such as surfboards or supports for offshore drilling equipment. Summary of the invention
[0005] Despite their conventional uses, Applicants have discovered that glass bubbles can be arranged and processed to produce particularly efficient porous structures with open porosity, such as for use in filters. Structures with open porosity can be formed by packing the glass bubbles tightly together so that the bubbles adhere to each other and also by causing the bubbles to breach (e.g., break, pop, break, open, expose the hollow core therein). The cavities of the individual glass bubbles open to each other to form porous cavities that extend throughout the structure and are interconnected and can have access to its surface. Such structures may be particularly useful for use in filters, or may be used for other purposes, such as providing a glass skeleton infiltrated with a polymer.
[0006] In some embodiments, a method of manufacturing a porous structure configured for use in a filter includes the steps of: cracking a plurality of glass bubbles (e.g., at least 100, at least 1000, at least 10,000 glass bubbles), and bonding the plurality of glass bubbles to each other. As a collection, the bonded cracked glass bubbles form a porous structure, wherein the cavities within the individual cracked glass bubbles are open to each other to form a cavity extending through the porous structure and reaching its surface. In some such embodiments, the cracking includes expanding the gas within the glass bubble so that the glass bubble breaks. In other such embodiments, the cracking includes devitrifying the glass of the glass bubble, wherein the softening and movement of the amorphous glass relative to the devitrified glass causes the glass bubble to break. In other such embodiments, the method includes heating the plurality of glass bubbles to at least the softening temperature of the amorphous glass of the glass bubbles. The heating may cause adjacent glass bubbles to sinter to each other. The cracking may occur simultaneously with the heating process. In some embodiments, the method includes the step of cooling the plurality of glass bubbles having adjacent glass bubbles directly physically bonded to each other. The time and temperature of heating and / or cooling can cause at least some of the glass of the glass bubbles to devitrify to form crystals. Applicants believe that devitrification can promote the rupture of the glass bubbles, for example by limiting the shrinkage of the glass bubbles under the negative pressure of the core.
[0007] In some such embodiments, before the heating step, the method for making a porous structure includes a step of extruding a green material comprising glass bubbles and an organic binder. Most of the glass bubbles survived the extrusion without breaking. In some such embodiments, the heating causes most of the organic binder from the porous structure to be burned off or chemically changed (by weight). During the heating process, the glass bubbles are heated as follows: the temperature is increased from ambient temperature to a first temperature with a first residence time; then the temperature is increased from the first temperature to a second temperature with a second residence time. The first temperature range may be 300°C to 400°C, and the first residence time range may be 1 to 10 hours. In some such embodiments, the second temperature is 600°C to 1200°C, and the second residence time is 1 to 10 hours. In other embodiments, the temperature is increased from the second temperature to a third temperature with a third residence time. In at least some of those embodiments, the second temperature is higher than 400°C and lower than the softening point of the amorphous glass of the glass bubbles, and the second residence time is 1 to 10 hours. The third temperature may be higher than a softening point of the amorphous glass of the glass bubbles, and the third residence time may be 1 to 10 hours.
[0008] Other exemplary embodiments include methods of making a porous structure, comprising the steps of: extruding a green material comprising glass bubbles and an organic binder, wherein a majority of the glass bubbles survive the extrusion without breaking; but then, causing a majority of the glass bubbles to crack after extrusion; and causing a plurality of glass bubbles to bond to each other. As a collection, the bonded cracked glass bubbles form a porous structure. In some embodiments, during the extrusion process, the glass bubbles have a D50 size of at least 1 micron but less than 100 microns, for example, a D50 size of at least 5 microns and not more than 50 microns. In some embodiments, after cracking, the porous structure comprising cracked glass bubbles has a pore size distribution (d50-d10) / d50 of less than 0.8. In some embodiments, during the extrusion process, the glass bubbles have an isostatic crushing strength of 1000 psi or more. In some embodiments, during the extrusion process, a majority of the glass bubbles have a pore size distribution of at least 0.1 g / cm 3 But less than 1.5g / cm 3 In some embodiments, during the extrusion process, the glass of the glass bubbles is soda-lime silicate, borosilicate and / or aluminosilicate.
[0009] Other exemplary embodiments include methods of making a porous structure, comprising the steps of: extruding a green material comprising glass bubbles and an organic binder, wherein a majority of the glass bubbles survive the extrusion without breaking; heating the glass bubbles to at least the softening temperature of the amorphous glass of the glass bubbles; after extrusion, causing a majority of the glass bubbles to break, wherein the breaking includes causing the gas within the glass bubbles to expand so that the glass bubbles break; and causing the glass bubbles to bond to each other, wherein the heating causes adjacent glass bubbles to sinter to each other. As a collection, the bonded, broken glass bubbles form a porous structure, wherein the cavities within the individual broken glass bubbles are open to each other to form cavities extending through the porous structure and to the surface thereof. In some such embodiments, the extruded green material floats in water, while the porous structure comprising the bonded, broken glass bubbles sinks.
[0010] In some embodiments, the porous structure includes a plurality of glass bubbles. The glass bubbles are sintered together so that adjacent glass bubbles are directly physically bonded to each other. Most of the glass bubbles are cracked and the cavities defined within the individual cracked glass bubbles are open to each other to form a cavity extending through the porous structure and reaching its surface. The porous structure has a porosity of at least 50% by volume. In some such embodiments, at least some of the glass of the glass bubbles is devitrified so that the glass contains crystals. In some embodiments, the porous structure is mainly glass (including devitrified glass) by weight, for example at least 90% of glass, and / or less than 75% of the porous structure is an amorphous phase, by weight. In some embodiments, the porous structure has a porosity of at least 65% and no more than 85%, by volume.
[0011] In other embodiments, the porous structure is primarily (e.g., at least 90% by weight) a plurality of broken glass bubbles sintered together so that adjacent glass bubbles are physically bonded directly to each other. The voids defined within the individual broken glass bubbles are open to each other to form a cavity extending through the porous structure and to its surface. In some such embodiments, the porous structure has a cell honeycomb geometry with a mesh thickness of no more than 9 mils, preferably no more than 8 mils, and more preferably no more than 6 mils, and a cell density of at most 300 cells per square inch, preferably at most 200 cells per square inch. Other embodiments include filters comprising such a porous structure and further comprising a coating supported by the porous structure, wherein the coating can be configured to block and / or attract target particles (i.e., a particle filter), and a shell at least partially surrounding the porous structure and the coating.
[0012] Other embodiments include an extrusion batch material for making a porous structure, comprising a plurality of glass bubbles, wherein the glass bubbles have a D50 size of at least 1 micron and no more than 100 microns, and wherein the glass bubbles have an isostatic crushing strength of 1000 psi or greater. The extrusion batch further comprises a binder and has a specific gravity of less than 1.0 relative to water. In some embodiments, the extrusion batch further comprises a pore former, such as an organic pore former (e.g., starch).
[0013] Other embodiments include porous structures that can be filter substrates or bodies (e.g., honeycombs) or can serve other purposes, such as providing support for liquid electrolytes or a framework for permeating polymers. The structure includes a plurality of glass bubbles having a D50 size of less than 100 microns. The glass bubbles are sintered to each other so that adjacent glass bubbles are directly physically bonded to each other. Most of the glass bubbles are cracked and the cavities defined within a single cracked glass bubble are open to each other to form a cavity extending through the structure and reaching its surface. In some embodiments, at least some of the glass of the glass bubbles is devitrified so that the glass contains crystals.
[0014] Other features and advantages are given in the following detailed description, some of which are readily understood by those skilled in the art or recognized by practicing the embodiments described in the text description and its claims and the accompanying drawings. It is to be understood that the above general description and the following detailed description are merely exemplary and are used to provide an overall review or framework for understanding the nature and characteristics of the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The accompanying drawings provide further understanding and are incorporated into and constitute a part of this specification. The drawings illustrate one or more embodiments and together with the detailed description are used to explain the principles and operations of the various embodiments. Therefore, the present disclosure will be better understood through the following detailed description in conjunction with the accompanying drawings, in which:
[0016] Figure 1 is a cross-sectional perspective view of a filter that may incorporate the technology disclosed herein.
[0017] Figure 2 is a perspective view of a porous structure (eg, a honeycomb) that may incorporate the technology disclosed herein.
[0018] Figure 3 is a perspective view of another structure that may incorporate the technology disclosed herein.
[0019] Figure 4 is a microscopic image of a green structure including glass bubbles according to an exemplary embodiment.
[0020] Figure 5 is a microscopic image of a green structure including glass bubbles according to another exemplary embodiment.
[0021] Figure 6 is similar to Figure 4 Microscope image of the structure, but the glass bubble has broken and devitrified.
[0022] Figure 7 is similar to Figure 5Microscope image of the structure, but the glass bubble has broken and devitrified. DETAILED DESCRIPTION
[0023] Before referring to the following detailed description and drawings that specifically set forth exemplary embodiments, it should be understood that the present technology is not limited to the details or methods described in the specific description or shown in the drawings. For example, it will be understood by those skilled in the art that the features and attributes associated with an embodiment shown in one of the drawings or described in text associated with one of the embodiments may be well applied to other embodiments shown in other drawings or described in other text.
[0024] See also Figure 1 , the assembly (shown as filter 110) includes: a porous structure 112 (e.g., substrate, body) in the form of a honeycomb and a housing 114 (e.g., frame) (e.g., metal can). The housing 114 at least partially surrounds the porous structure 112. More specifically, Figure 1 The housing 114 is shown in cross-section, with a portion removed to show the porous structure 112 in the housing 114. In some embodiments, the porous structure 112 can be coated, such as with a coating configured to attract or otherwise affect target particles (e.g., exhaust emissions, airborne particles, volatile organic compounds). For example, a substrate in a catalytic converter assembly can receive a washcoat comprising aluminum oxide, titanium, and silicon dioxide, and can be coated with a catalyst comprising a precious metal (e.g., platinum).
[0025] See also Figure 2 , you can use something like Figure 1 The porous structure 210 of the porous structure 112 is used in the filter 110 or anywhere else. The porous structure 210 is "honeycomb" in that the porous structure 210 includes elongated channels 212 that extend generally through at least a portion of the porous structure 210, such as linearly extending from an outer surface 214 (e.g., a face) of the porous structure 210 to at or near an opposite outer surface of the porous structure 210. In some embodiments, the filter 110 may include blockages, wherein air flows through the walls and mesh of the filter but particles are captured. In other embodiments, some or all of the elongated channels 212 are not blocked, allowing fluid (e.g., exhaust, water, etc.) to flow through the elongated channels 212. In other embodiments, the porous structure may be porous but not include elongated channels 212 (see generally Figure 3 ).
[0026] According to an exemplary embodiment, the elongated channel 212 can have a high aspect ratio (e.g., length-to-width ratio or length-to-diameter ratio), wherein the length L is oriented along the flow path of the elongated channel 212 between the openings of the elongated channel 212 provided on the outer surface 214 of the porous structure 210 on the opposite outer surface 214, such as Figure 2 According to an exemplary embodiment, the elongated channels 212 are elongated such that at least some (e.g., a majority, >90%, all) of the channels have an aspect ratio (defined as the length of the elongated channel 212 relative to the widest cross-sectional dimension of the corresponding elongated channel 122 perpendicular to the length L) of at least 10, at least 20, at least 50, at least 100, and / or no more than 50,000.
[0027] Although Figure 1-2 The porous structures 112, 210 are shown as having a generally cylindrical geometry, but other geometries are contemplated, such as cubes, cuboids, sheets, or more complex geometries. Figure 3 , structure 310 is a generally rectilinear sheet that can be used as a filter substrate or for other purposes. In some embodiments, Figure 3 The structure 310 can have a generally uniform density and a non-homogeneous pore distribution, particularly for glass foam sheets without elongated channels. The foam can be: highly porous, coated, and / or partially or completely filled with a liquid material (e.g., an electrolyte), a solid material (e.g., a dielectric), or anything else.
[0028] According to an exemplary embodiment, structure 310 is highly porous, and the pores (e.g., cavities, voids, spaces between structures) are open to each other, such that fluids can flow through the pores into and through structure 310. However, in some such embodiments, structure 310 may be only semi-permeable, allowing only some fluids and / or smaller particles to pass through structure 310, but trapping or blocking others.
[0029] According to an exemplary embodiment, a structure (e.g., Figure 1-3 The porous structures 112, 210, and structures 310) may include a plurality of glass bubbles and / or may be formed at least in part of a plurality of glass bubbles (e.g., hollow microspheres, see Figure 5 and 7512, 512'), wherein "plurality" may include more than 100, such as more than 1000. In some such embodiments, the glass bubbles may have a D50 size of at least 1 micrometer (μm) and no more than 1000 μm, such as at least 5 μm, at least 25 μm and / or no more than 500 μm, such as no more than 250 μm, such as no more than 100 μm, obtained by ASTM standards (e.g., D4284-12). In some such embodiments, the porous structure containing the glass bubbles has a pore size distribution (d50-d10) / d50 of less than 0.8, such as less than 0.4, such as less than 0.2, such as less than 0.1, such as less than 0.06. In some embodiments, (as discussed below, before the breach) a majority of the glass bubbles have a pore size distribution of at least 0.1 g / cm 3 Density, for example at least 0.3 g / cm 3 and / or less than 1.5g / cm 3 , for example, less than 0.7 g / cm 3 , where density considers the mass per volume, including the internal bubble volume.
[0030] According to an exemplary embodiment, the porous structures 112, 210, and 310 are primarily glass or crystallized glass (glass ceramic, ceramic) by weight, e.g., at least 70% by weight, e.g., at least 80%, and e.g., at least 90%. For those in the industry, it may be surprising or counterintuitive that such a large proportion of the structures 112, 210, 310 is formed of glass or crystallized glass of glass bubbles, as they may expect such structures to be particularly fragile and / or not held together at all. However, in some intended uses, the porous spaces of the porous structures 112, 210, and 310 may be later at least partially filled with other materials (e.g., fluids), while the porous structures 112, 210, and 310 are largely held together due to the methods of making such structures as taught herein.
[0031] Figure 4-5 The structure 410, 510 includes a "green body" (e.g., before firing, before sintering). More specifically, Figure 4 The green structure 410 may be a porous structure (e.g., Figure 1 The outer wall of the honeycomb porous structure shown. Figure 5 The green structure 510 may be a porous structure (e.g., Figure 1 The inner wall or mesh material of the honeycomb body shown.
[0032] A green structure may be formed from the extruded batch material. According to an exemplary embodiment, the green structure 410, 510 includes glass bubbles 412, 512 held in a binder 414, 514 (e.g., an organic binder or a primarily organic binder). In some embodiments, the batch material may include glass bubbles having a particle size of 3 to 100 microns, such as a particle distribution (d90-d10) / d90 of less than 2, such as less than 1.5 or less than 1. According to an exemplary embodiment, the batch density (e.g., a "wet batch" density) is less than 1.5 g / cm 3 , for example, less than 1.0 g / cm 3 , for example, less than 0.5 g / cm 3 , for example, less than 0.3 g / cm 3 According to an exemplary embodiment, Figure 4-5 The green and batch materials are buoyant (i.e., have a specific gravity less than 1 compared to water), whereas the finished porous structure may sink after the glass bubble is fired and / or breached (see Figure 6-7 ).
[0033] In some embodiments, the green structures 410, 510 may also include a slip agent and / or lubricant, such as oils. Sodium stearate or other sintering aids may be added to the batch. In some embodiments, the binder may include methylcellulose. In some embodiments, the batch may also include a pore former, such as an organic pore former, such as starch (e.g., corn starch, pea starch). According to an exemplary embodiment, the glass bubbles 412, 512 may be a "free-standing" composition, based on the inorganic composition components (>90 wt% inorganic in the batch, >95 wt%, skeleton). In other embodiments, the batch may also include a second inorganic material having a softening temperature higher than the glass bubbles, such as clay, talc, silica, alumina, minerals, synthetic oxides, other types of glass or ceramic particles and / or bubbles.
[0034] In some embodiments, particularly resilient glass bubbles 412, 512 are used, such as those having a median isostatic crushing strength of at least 1000 psi, such as at least 2000 psi, such as at least 3000 psi (see Yun and Shou, "Measuring Isostatic Pressing Strength of Hollow Glass Microspheres by Mercury-injection Apparatus", Key Engineering Materials, No. 544, pp. 460-5 (2013)). In addition, the rate and pressure through the corresponding extruder can vary depending on the size of the glass bubbles, their materials, and the extrusion apparatus. In some embodiments, the extrusion pressure range is less than 2500 psi, such as less than 2000 psi and / or at least 500 psi.
[0035] According to an exemplary embodiment, the glass bubbles 412, 512 in the binder 414, 514 are extruded (e.g., in a twin-screw manner) at a rate and pressure that preserves the integrity of a majority (e.g., greater than 50%, greater than 75%, greater than 90%) of the glass bubbles 412, 512. Figure 4-5 As shown, most of the glass bubbles 412, 512 appear to be completely intact. In this regard, in other contemplated embodiments, the extrusion rate and pressure can preserve the integrity of many (but not most, e.g., less than 50%, but at least 25% or at least 20%) of the glass bubbles. Preserving the integrity of the glass bubbles 412, 512 allows the glass bubbles to occupy a larger volume of space in the green structure 410, 510, with cavities between and within the glass bubbles 412, 512.
[0036] Extruding the green structure 410, 510 may be useful in porous structures (e.g., Figure 1 A through-channel is formed in a porous structure of a honeycomb shape (for example, Figure 2 The elongated channels 212 shown) or other regular features in the corresponding green structures 410, 510 are particularly effective. However, in other contemplated embodiments, such structures comprising glass bubbles in a binder can be molded, cast, or formed or processed in any other manner, which can better or alternatively preserve the integrity of the glass bubbles 412, 512. In other contemplated embodiments, structures such as structure 310 that are significantly different in shape from porous structures 112, 210 can be extruded or otherwise formed.
[0037] The glass bubbles 412, 512 may include glass (e.g., by volume, consisting of glass, consisting essentially of glass, including glass), such as soda-lime silicate glass, borosilicate, or other glass. The glass of the glass bubbles 412, 512 may be completely amorphous, crystalline, polycrystalline, etc., such as a two-phase glass ceramic. In some embodiments, the glass of the glass bubbles 412, 512 may be amorphous prior to heating, and may subsequently devitrify and / or crystallize. For purposes of clarity, "glass" as used herein includes amorphous glass, devitrified glass having crystals (e.g., glass ceramics and crystalline phases). In at least some contemplated embodiments, the glass bubbles 412, 512 may include and / or be formed of other materials, such as synthetic materials, polymers, ceramics, fly ash, floating beads, metals, etc.
[0038] According to an exemplary embodiment, glass bubbles having high crystallinity at the softening temperature of the glass bubbles (e.g., containing more than 45 wt. % SiO 2 and / or CaSiO 3 The glass bubbles (such as those of the glass bubbles ... 2 , more than 6.5% CaO, less than 7% and at least some B 2 O 3 , less than 1% and at least some Al 2 O 3 , at least some Fe 2 O 3 , less than 2.5% and at least some Na 2 O, and / or at least some K 2 O. In some embodiments, the glass of the glass bubbles is, is primarily, or comprises: soda-lime silicate glass, borosilicate glass, and / or aluminosilicate glass. Tables 1 and 2 below provide some exemplary compositions and corresponding glass bubble properties:
[0039] Table 1: Exemplary Glass Bubble Compositions
[0040] sample A1 A2 A3 A4 A5 B1 B2 <![CDATA[SiO 2 ]]> 79.4 79.3 79.3 79.3 79.5 73.6 71.1 CaO 7.72 7.43 7.43 7.43 7.89 6.19 5.67 <![CDATA[B 2 THE 3 ]]> 5.95 5.95 5.95 5.95 5.09 7.38 8.73 <![CDATA[Al 2 THE 3 ]]> 0.52 0.55 0.55 0.55 0.49 1.01 1.07 <![CDATA[Fe 2 THE 3 ]]> 0.057 0.056 0.056 0.056 0.035 0.089 0.081 <![CDATA[Na 2 The]]> 1.68 1.59 1.59 1.59 1.74 2.58 2.60 <![CDATA[K 2 The]]> 0.14 0.14 0.14 0.14 0.14 0.19 0.21
[0041] Table 2: Properties of glass bulbs
[0042] sample A1 A2 A3 A4 A5 B1 B2 Softening temperature(℃) ~800 ~800 ~800 ~800 ~800 ~600 ~600 <![CDATA[Density (g / cm 3 )]]> 0.38 0.60 0.64 0.55 0.48 0.45 0.34 Porosity(%) 82.9 73.1 71.3 75.3 78.4 79.8 84.8 Shell thickness (μm) 1.07 1.45 1.18 1.76 0.91 0.70 1.24 <![CDATA[Particle size D 10 (μm)]]> 21.1 17.0 15.2 27.9 15.0 10.5 21.9 <![CDATA[Particle size D 50 (μm)]]> 35.5 28.7 22.2 39.1 23.4 19.2 35.1 <![CDATA[Particle size D 90 (μm)]]> 58.3 58.9 33.5 58.9 37.0 35.4 55.4 <![CDATA[(Distribution (D 90 -D 10 ) / D 50 > 1.05 1.45 0.83 0.79 0.94 1.30 0.95 Crushing strength (psi) 3000 10000 4000 3000 4000
[0043] According to an exemplary embodiment, the green structure 410, 510 is heated (e.g., fired in a furnace, laser heated). The heating may burn off the binder 414, 514, char the binder 414, 514, chemically transform the binder 414, 514, or otherwise affect the binder 414, 514. According to an exemplary embodiment, the green structure 410, 510 is heated to at least the softening temperature of the glass of the glass bubbles 412, 512. However, the glass bubbles 412, 512 are not overheated (e.g., much above the liquidus temperature), in which case the glass bubbles 412, 512 may completely lose cohesion or structure. Depending on the material, the heating may be at least 400°C, at least 600°C, at least 800°C, at least 1200°C, and / or no more than 2000°C, such as no more than 1600°C, such as no more than 1400°C. In contemplated embodiments, the glass bubbles 412, 512 may have other softening temperatures.
[0044] According to exemplary embodiments, the conditions and operation of the green structures 410, 510 during heating are such that adjacent glass bubbles 412, 512 physically interact with each other, such as directly bond (e.g., sinter, weld, melt) to each other, but do not completely lose their respective structures. In other words, in at least some such embodiments, the conditions and operation are such that the glass bubbles 412, 512 do not completely liquefy and / or completely lose structure, but instead become bonded to each other such that the resulting structure in the aggregate is cohesive and rigid.
[0045] According to other such exemplary embodiments, the conditions and operation of the green structure 410, 510 during heating can cause a number of the glass bubbles 412, 512 (e.g., a majority, >90%, >95%, >99%) to breach or break, such as due to internal gas expansion and / or due to devitrification or rupture in other ways. In some such embodiments, the glass bubbles 412, 512 are heated to a point where the glass bubbles 412, 512 lose integrity and the glass of the glass bubbles 412, 512 shatters or otherwise breaches. In other contemplated embodiments, the glass bubbles can be breached by microwaves, acoustic energy, or other phenomena.
[0046] The breaching of the glass bulb 412, 512 may be counter-intuitive to those in the industry who may rely on the glass bulb to provide buoyancy and / or prevent material from flowing into or through the void within the glass bulb. However, applicants have discovered that by breaching the glass bulb 412, 512 of the structures as disclosed herein, the voids of the glass bulb 412, 512 can be maintained and / or even enlarged and joined to one another.
[0047] After heating, the green structure 410, 510 may be cooled, e.g., to a temperature at least 100° C. below the heating temperature of the green structure 410, 510, e.g., below 100° C., e.g., below 50° C. During cooling, adjacent glass bubbles 412, 512 (which may be less spherical at this point) are and / or remain physically bonded to one another, e.g., directly or indirectly (via an intermediate binder).
[0048] In some such embodiments, cooling includes dwelling at a temperature above room temperature (e.g., the annealing point of the glass of the glass bubble) but below the heating temperature. In some embodiments, the dwell may be in incremental steps, or in other embodiments, may be in the form of a very gradual temperature drop within a certain temperature range, both of which may allow for the formation of crystals in the material of the glass bubble 412, 512 and / or may facilitate the relaxation of residual stresses through annealing.
[0049] Similarly, the applicant has discovered a unique firing process that causes the glass bubble to crack and / or open. During the heating process, the glass bubble can be heated from ambient temperature to a first temperature (e.g., a fixed temperature and / or multiple temperatures within a defined range) with a first residence time, for example: wherein the first temperature is at least 200°C, for example, 300°C to 400°C and / or wherein the first residence time is at least 1 minute, for example, 1 to 10 hours. In some such embodiments, the temperature is then increased from the first temperature to a second temperature, with a second residence time, for example: wherein the second temperature is greater than 400°C, for example, 600°C to 1200°C, and wherein the second residence time is also at least 1 minute, for example, 1 to 10 hours. In some embodiments, during the heating process, the temperature is increased from the second temperature to a third temperature, with a third residence time, for example: wherein the second temperature is greater than 400°C and less than the softening point of the glass of the glass bubble 412, 512, and the third temperature is greater than the softening point of the glass of the glass bubble. The third residence time can be at least 1 minute, for example, 1 to 10 hours.
[0050] See now Figure 6-7 , Figure 6-7 The structures 410', 510' are related to the green structures 410, 510. More specifically, Figure 6 The structure 410' may be a porous structure (e.g., Figure 1 The outer wall of the honeycomb shown in FIG. Figure 7 The structure 510' may be a porous structure (e.g., Figure 1The structure 410', 510' is not a "green" structure. Instead, the shells or outer shells of the glass bubbles 412', 512' are bonded to each other and the glass bubbles 412', 512' are split, wherein the interior volume of the glass bubbles 412', 512' is exposed and the spaces between the glass bubbles 412', 512' are open and interconnected, forming cavities 416', 516' (tortuous paths) that extend through the entire structure 410', 510' and reach the surface.
[0051] See also Figure 6-7 In some contemplated embodiments (e.g., where particularly small glass bubbles are used), the inner walls formed between the holes in structures 112, 210, 310 can be particularly thin, e.g., having a thickness less than 1 millimeter (mm), e.g., less than 500 micrometers (μm), e.g., less than 100 μm, e.g., less than 50 μm, e.g., less than 10 μm, e.g., less than 5 μm, as discussed below.
[0052] from Figure 6-7 It can be seen that in some embodiments, the glass of the glass bubbles 412', 512' devitrifies and forms crystals. Figure 6-7 In the embodiment of the present invention, devitrified glass appears light gray. Gradual heating and dwelling as disclosed herein can facilitate crystal growth, which can make the resulting structures 410', 510' strong. Although the green material can include amorphous glass bubbles, the processed structure after firing can be a glass-ceramic with a crystallinity of more than 45% by weight (e.g., at least 50% by weight; e.g., at least 64% by weight crystallinity). In some embodiments, the porous structure (after firing) is mainly composed of glass (including devitrified glass), e.g., at least 90% of glass, by weight. In some such embodiments, the porous structure is composed of less than 55% by weight of an amorphous phase. Figure 6 It can be seen that the white needle-like structures on the surface of the just-fired state may be tridymite crystals.
[0053] See also Figure 7 , the cavities 416', 516' formed by the broken glass bubbles 412', 512' and / or due to the adhesive (see Figure 4-5 The voids left by the burning away of the binder 414, 514) can lead to a particularly high porosity of the resulting structure 410', 510'. Applicants believe that the technology disclosed herein provides high porosity, for example: at least 40%, at least 60%, at least 70%, at least 80%, by volume (see ASTM D6761-07). According to exemplary embodiments, the porous structures 112, 210 and structure 310 have a porosity of at least 65% and / or no more than 85%, by volume.
[0054] Although Figure 4-7 The microstructures and surface features shown in accordance with at least some exemplary embodiments, however, the porous structures 112, 210, and 310 may have at least 1 cubic centimeter (cm3) within their outer surface. 3 ) of a total volume, for example at least 2 cm 3 , for example at least 10 cm 3 , for example at least 50cm 3 , and / or not more than 2000cm 3 , for example, not more than 1000cm 3 ; However, in other embodiments, the volume can be much larger, such as for large frontal area filters.
[0055] In contemplated embodiments, the processes and techniques disclosed herein are used for honeycomb filters, such as diesel engine particulate filters. Glass bubbles are selected to have sufficient crush strength and sufficiently small geometry to facilitate extrusion of a honeycomb having at least 50 cells per square inch (e.g., at least 100 cells per square inch, such as at least 200 cells per square inch, such as at least 300 cells per square inch) and / or a web thickness of no more than 10 mils (i.e., one thousandth of an inch) (e.g., no more than 8 mils, such as no more than 7 mils, such as no more than 6 mils, such as no more than 5 mils), for example, a cell geometry of: 8, 100 / 7, 100 / 6, 100 / 5, 50 / 8, 50 / 7, 50 / 6, etc. The web may have a thickness of at least 200 / 8, less than 200 / 8, 100 / 7, 100 / 6, 100 / 5, 50 / 8, 50 / 7, 50 / 6, etc., or may have a thickness of at least 200 / 8, 100 / 7, 100 / 6, 100 / 5, 50 / 8, 50 / 7, 50 / 6, etc.
[0056] At least some such embodiments have a cylindrical geometry with a diameter of at least 4 inches, such as at least 6 inches, such as at least 8 inches, such as at least 12 inches, such as at least 24 inches, and / or no more than 64 inches, such as no more than 36 inches. Other such embodiments have a cross-section having a generally square, rectangular, or other polygonal geometry with sides of at least 4 inches, such as at least 6 inches, such as at least 8 inches, such as at least 12 inches, such as at least 24 inches, and / or no more than 64 inches, such as no more than 36 inches. Other contemplated embodiments have other sizes or shapes. Such geometries can contribute to low pressure drop, high dust loading, and high filtration efficiency.
[0057] The porous structure, assembly and structure shown in various exemplary embodiments are only schematic. Although only some embodiments are described in detail in the present disclosure, many improvements are feasible (for example, the size, scale, structure, shape and ratio of various elements, parameter values, installation arrangements, use of materials, colors, orientations), which do not essentially deviate from the novelty teachings and advantages of the subject matter described herein. Some elements shown as integrally formed can be composed of multiple parts or elements, and the position of the elements can be reversed or otherwise changed, and the properties or quantity of discrete elements or positions can be changed or altered. The order or sequence of any process, logical algorithm or method steps can be changed or reordered according to the embodiments replaced. Without departing from the scope of the present invention, the design, operating conditions and arrangement of various exemplary embodiments can be replaced, modified, changed and omitted.
Claims
1. A method of making a porous structure configured for use in a particulate filter, comprising: heating the plurality of glass bubbles to at least a softening temperature of an amorphous glass of the glass bubbles; bonding a plurality of glass bubbles to one another by sintering caused by heating, wherein the glass bubbles have a D50 particle size of at least 1 micrometer but no more than 100 micrometers, and wherein the plurality includes at least 1000 glass bubbles; and causing the glass bulb to fracture, wherein the fracture occurs while heating; wherein, as an aggregate, the bonded ruptured glass bubbles form a porous structure, wherein cavities within the individual ruptured glass bubbles are open to each other to form cavities extending through the porous structure and to a surface thereof, and wherein, by weight, the porous structure is primarily composed of glass.
2. The method of claim 1, further comprising devitrifying at least some of the glass of the glass bubble to form crystals.
3. The method of claim 2, wherein: The rupture includes the flow of amorphous glass relative to the crystal of the glass bubble.
4. The method of claim 1, wherein: The heating causes adjacent glass bubbles to sinter to each other.
5. The method of claim 1, further comprising cooling the plurality of glass bubbles while adjacent breached glass bubbles are physically bonded directly to each other.
6. The method of claim 1, further comprising extruding the green material comprising glass bubbles and an organic binder prior to heating, wherein: Most of the glass bubbles survived the extrusion without breaking.
7. The method of claim 6, wherein: Extrusion involves extruding thousands of glass bubbles connected to each other by an organic binder.
8. The method of claim 7, wherein: The heating causes most of the organic binder by weight to be burned off or chemically transformed.
9. The method of claim 1, wherein: During the heating process, the glass bubble is heated to a first temperature range for a first dwell time, and then heated to a second temperature range for a second dwell time; Wherein, the first temperature range is 300° C. to 400° C.; and The first residence time ranges from 1 to 10 hours.
10. The method of claim 9, wherein: During the heating process, the second temperature range is 600° C. to 1200° C.; and The second residence time ranges from 1 to 10 hours.
11. The method of claim 9, wherein: During the heating process, the second temperature range is higher than 400° C. and lower than the softening point of the amorphous glass of the glass bubble; Wherein, the second residence time ranges from 1 to 10 hours; wherein, during the heating process, the glass bulb is heated to a third temperature range for a third dwell time; Wherein, the lower limit of the third temperature range is the softening point of the amorphous glass; and The third residence time ranges from 1 to 10 hours.
12. The method of claim 1, comprising: A green material comprising glass bubbles and an organic binder is extruded, wherein a majority of the glass bubbles survive the extrusion without breaking.
13. The method of claim 12, wherein: During extrusion, the glass bubbles have a D50 particle size of at least 1 micron but less than 100 microns.
14. The method of claim 12, wherein: During extrusion, the glass bubbles have a D50 particle size of at least 5 and no more than 30 microns.
15. The method of claim 12, wherein: After cleaving and bonding, the glass bubbles have a pore size distribution (d50-d10) / d50 of less than 0.
8.
16. The method of claim 12, wherein: During extrusion, the glass bubbles have an isostatic crush strength of 1000 psi or more.
17. The method of claim 12, wherein: During extrusion, most of the glass bubbles have a density of at least 0.1 g / cm 3 But less than 1.5g / cm 3 density.
18. The method of claim 12, wherein: The glass of the glass bubbles includes soda-lime silicate glass, borosilicate glass and / or aluminosilicate glass.
19. A porous structure manufactured by the method of claim 1, comprising: Multiple glass bubbles; wherein the glass bubbles are sintered to each other so that adjacent glass bubbles are directly physically bonded to each other; Among them, most of the glass bubbles are cracked; wherein the cavities defined within the glass bubbles of the single breach are open to each other to form a cavity extending through the porous structure and reaching the surface thereof; wherein the porous structure has a porosity of at least 50% by volume; and Therein, the porous structure consists mainly of glass by weight.
20. The porous structure of claim 19, wherein: At least some of the glass of the glass bubble is devitrified such that the glass includes crystals.
21. The porous structure of claim 19, wherein: The porous structure is composed of at least 90% glass by weight.
22. The porous structure of claim 19, wherein: The porous structure is composed of less than 75% by weight of the amorphous phase glass.
23. The porous structure of claim 19, wherein: The porous structure has a porosity of at least 65% and no more than 85% by volume.
24. A porous structure made by the method of claim 1, consisting essentially of a plurality of broken glass bubbles, by weight, sintered together so that adjacent glass bubbles are directly physically bonded to each other, wherein: The voids defined within the individual ruptured glass bubbles are open to one another to form cavities extending through the porous structure and to the surface thereof.
25. The porous structure of claim 24, wherein: The porous structure is composed of at least 90% glass by weight.
26. The porous structure of claim 24, wherein: The porous structure has a cell honeycomb geometry with a web thickness not exceeding 10 mils and a cell density not exceeding 400 cells per square inch.
27. A filter comprising the porous structure according to claim 24; A coating supported by a porous structure, wherein The coating is configured to influence, block and / or attract target particles; as well as An outer shell at least partially surrounds the porous structure and the coating.
Citation Information
Patent Citations
Method utilizing hollow micro-spheres to prepare foamed ceramic provided with communicated hole walls
CN109095948A
Open-cell glass crystalline porous material
US6444162B1